Brevilin A Ameliorates Acute Lung Injury and Inflammation Through Inhibition of NF-κB Signaling via Targeting IKKα/β - Liu, Lu; Chen, Xian; Jiang, Yifang; Yuan, Yun; Yang, Luyao; Hu, Qiongying; Tang, Jianyuan; Meng, Xianli; Xie, Chunguang; Shen, Xiaofei (Frontiers in Pharmacology, 2022)
Acute lung injury (ALI) is life-threatening disease characterized by uncontrolled inflammatory response. IKKα/β, the key kinases in the activation of NF-κB pathway, are implicated in inflammatory pulmonary injury, and represent attractive targets for ALI therapy. Brevilin A (BVA) is a sesquiterpene lactone from Centipeda minima, a Chinese herb that is used to treat inflammatory diseases. This study aims to investigate the inhibition of BVA on ALI, with focus on clarifying the molecular mechanisms involved in BVA-mediated anti-inflammatory activity in macrophages. Briefly, BVA significantly inhibited the production of NO and PGE2 by suppressing iNOS and COX2 expression, and suppressed the mRNA expression of IL-1β, IL-6, and TNFα in LPS/IFNγ-stimulated RAW264.7 macrophages. The anti-inflammatory activity of BVA was further confirmed in LPS/IFNγ-stimulated BMDMs and TNFα/IFNγ-exposed RAW264.7 cells. In vivo, BVA effectively attenuated LPS-induced lung damage, inflammatory infiltration, and production of pro-inflammatory cytokines, including MPO, IL-1β, IL-6, TNFα, and PGE2. Mechanistically, BVA could covalently bind to the cysteine 114 of IKKα/β, and effectively inhibiting the activity and function of IKKα/β, thereby resulting in the suppression of phosphorylation and degradation of IκBα and the subsequent activation of NF-κB signaling. Furthermore, pretreatment of DTT, a thiol ligand donor, significantly abolished BVA-mediated effects in LPS/IFNγ-stimulated RAW264.7 cells, suggesting the crucial role of the electrophilic α, β-unsaturated ketone of BVA on its anti-inflammatory activity. These results suggest that BVA ameliorates ALI through inhibition of NF-κB signaling via covalently targeting IKKα/β, raising the possibility that BVA could be effective in the treatment of ALI and other diseases harboring aberrant NF-κB signaling.